Comparative Analysis of Semi Rigid Ureterolithotripsy and Extracorporeal Shock Wave Lithotripsy for the Treatment of Upper Ureteric Calculi - Ullah, Atm Aman; Shameem, Isteaq Ahmed; Alam, Akm Khursidul; Chowdhury, Md Golam Mowla; Islam, Akm Anwarul; Kibria, Samg (Bangladesh Journal of Urology, 2020)
Objectives: To find out the better treatment option between semi rigid ureteroscopy with ICPL and ESWL for upper ureteric calculi. To compare stone free rate, complications and re treatment between ureterolithotripsy and ESWL in upper ureteric calculi. Materials and Method: This prospective comparative study was conducted in the department of urology BSMMU and Kidney and urology hospital, Dhaka from June 2009 to May 2010. Fifty patients were enrolled and 25 on each group as ESWL and ICPL Inclusion criteria was adult patients with single radiopaque stone of 06-15 mm, and no obstruction distal to stone. We exclude Stone size > 1.5cm, PUJ stone, patients with DJ stent and nephrostomies, infection, pregnancy, hemostatic, disorders, and morbid obesity. Identified postoperative urological complications pain, haematuria, fever, stone migration, obstruction, infections, and postoperative hospital stays recorded accordingly. X- ray KUB and in some cases ultrasound of kidney ureter and bladder with prostate with PVR were done. Those with residual calculi sized less than 2 mm were considered stone free. Those patients whom stone not cleared or stone migrated they again sent for ESWL or ureterolithotripsy. Stone free patient of ureterolithotripsy sent for removal of Double J stent under local anesthesia at 4 weeks. Results: Three months postoperatively, 21 out of 25 Patients (85%) in the ureterolithotripsy group were stone free. In ureterolithotripsy group, all failures were due to upward calculus migration. After calculus migration, this was mandated double- J stenting and send for ESWL. These patients were referred for ESWL, all of whom were stone free after this procedure. DJ stent removed under local anesthesia. 22 out of 25 Patients (88%) in the ESWL group were stone free and 10 patients need two sessions. Re-ESWL had done after 3 weeks. All failures in ESWL group were due to hard in constancy and small stone size. Failed cases were referred for ureterolithotripsy and DJ stenting, all of whom were stone free after this procedure. Using statistical data by chi square test and analytical test level of significance as set at 0.05 and p< 0.05 was consider significant. Conclusion: Upper ureteral calculi up to 1.5 cm can be safely and effectively managed by using semi rigid ureteroscopy and pneumatic lithotripsy. However, the ESWL approach has still its role in treating upper ureteric calculi. Finally, postoperative home rest in the ESWL group was more due to the repeated treatment. Bangladesh Journal of Urology, Vol. 20, No. 2, July 2017 p.54-60